Uterine carcinosarcoma: report of a case and current management - Sánchez Gutiérrez, Lourdes (2014)
Uterine carcinosarcomas (previously called malignant Müllerian mixed tumors) are rare malignant and highly aggressive neoplasias. A case of a rapid progression uterine carcinosarcoma is reported, and differential diagnosis and treatment are discussed.